Evaluation of classical training at the ambon religious education and training center using the kirkpatrick evaluation model - Riana Antika Amahoroe (Balai Diklat Keagamaan Ambon, 2023)
The purpose of this study was to evaluate classical training (regular training and training in work areas) held by BDK Ambon using the level 1 and level 2 Kirkpatrick models. MTs in the Aru Islands. Based on the results of the Level 1 Evaluation, showed a positive reaction from the training participants with an average participant rating of regular training providers of 94.21 and 95.88 for training in the work area. The training participants were satisfied with the performance of the Ambon BDK training organizers. The highest score is in the aspect of participation in the determination of participants, namely 96.79 for regular training and 97.36 for training in work areas. Furthermore, the participant's assessment of the trainer showed an overall average score of 95.98 for regular training at BDK Ambon and 96.98 for training in work areas. These results indicate that the participants consider that the trainers is very competent, the training environment is very comfortable, and the methods used are effective in delivering training materials. Furthermore, based on the results of the level 2 evaluation regarding learning, it can be concluded that there has been an increase in knowledge, skills, and attitudes after attending the training. It can be ensured that training alumni not only have theoretical knowledge but are also able to apply it in practice. This can be seen from the training products in the form of learning videos, interactive quizzes, and learning blogs as well as Google Classroom as learning media made by participants during the training.